Konfliktbeilegung - Kamp, Hermann (Handwörterbuch zur deutschen Rechtsgeschichte)

Die Funktionseliten und die Aufstände in den burgundischen Territorien nach dem Tod Karls des Kühnen - Kamp, Hermann („Armer Konrad“ und Tübinger Vertrag im interregionalen Vergleich. Fürst, Funktionseliten und „Gemeiner Mann“ am Beginn der Neuzeit)

Soziologie der Mediation aus historischer Perspektive - Kamp, Hermann (Zeitschrift für Rechtssoziologie)

Politik statt Triumph? Zum Umgang Philipp Augustus‘ mit dem Sieg von Bouvines - Kamp, Hermann (Bouvines 1214 – 2014: Eine Schlacht zwischen Geschichte und Erinnerung. Deutsch-französische Ansätze und Vergleiche)

Focus on Evidence: Schlussfolgerungen für Lehrerbildung und Fremdsprachenunterricht - Hohwiller, Peter (Focus on Evidence – Fremdsprachendidaktik trifft Neurowissenschaften)

Peer teaching in den drei Phasen der Lehrerbildung - Hohwiller, Peter (Sprachen lehren)

Human-Machine Autonomies - Weber, Jutta; Suchman, Lucy (Autonomous Weapon Systems. Law, Ethics, Policy)

Keep Adding. Kill Lists, Drone Warfare and the Politics of Databases - Weber, Jutta (Environment and Planning D. Society and Space. Special Issue on ‚The Politics of the List: Law, Security, Technology‘ (Hg.: Marieke de Goede/Anna Leander/Gavin Sullivan))

ProfiLe-P+ – Professional Competence in Academic Physics Teacher Education - Vogelsang, Christoph; Borowski, Andreas; Fischer, Hans; Kulgemeyer, Christoph; Reinhold, Peter; Riese, Josef; Schecker, Horst

Ethical Regulations on Robotics in Europe - Weber, Jutta; Nagenborg, Michael; Capurro, Rafael; Pingel, Christoph (Machine Ethics and Robot Ethics)

Direct measurement of wall slip and slip layer thickness of non-Brownian hard-sphere suspensions in rectangular channel flows - Jesinghausen, Steffen; Weiffen, Rene; Schmid, Hans-Joachim (Experiments in Fluids)
Wall slip is a long-known phenomenon in the field of rheology. Nevertheless, the origin and the evolution are not completely clear yet. Regarding suspensions, the effect becomes even more complicated, because different mechanisms like pure slip or slip due to particle migration have to be taken into account. Furthermore, suspensions themselves show many flow anomalies and the isolation of slip is complicated. In order to develop working physical models, further insight is necessary. In this work, we measured experimentally the wall slip velocities of different highly filled suspensions in a rectangular slit die directly with respect to the particle concentration and the particle size. The slip velocities were obtained using a particle image velocimetry (PIV) system. The suspensions consisting of a castor oil–cinnamon oil blend and PMMA particles were matched in terms of refractive indexes to appear transparent. Hereby, possible optical path lengths larger than 15 mm were achieved. The slip velocities were found to be in a quadratic relation to the wall shear stress. Furthermore, the overall flow rate as well as the particle concentration has a direct influence on the slip. Concerning the shear stress, there seem to be two regions of slip with different physical characteristics. Furthermore, we estimated the slip layer thickness directly from the velocity profiles and propose a new interpretation. The PIV technique is used to investigate the viscosity and implicit the concentration profile in the slit die. It is shown that the particle migration process is quite fast.
Keywords: Rheology; Wall Slip; Slip; apparent slip; suspension

Hans Werner Henze - Tumat, Antje (Lexikon der Oper)

Projekt WiGeMath: Wirkung und Gelingensbedingungen von Unterstützungsmaßnahmen für mathematikbezogenes Lernen in der Studieneingangsphase - Colberg, Christoph; Schürmann, Mirko; Biehler, Rolf; Hochmuth, Reinhard Karl; Schaper, Niclas; Liebendörfer, Michael (Working Paper Studieneingangsphase Perspektiven aus der Begleitforschung zum Qualitätspakt Lehre)

Wirkung und Gelingensbedingungen von Unterstützungsmaßnahmen für mathematikbezogenes Lernen in der Studieneingangsphase - Colberg, Christoph; Biehler, Rolf; Hochmuth, Reinhard; Schaper, Niclas; Liebendörfer, Michael; Schürmann, Mirko (Beiträge zum Mathematikunterricht 2016)

Fallbeispiele im Herforder Rechtsbuch im Kontext der Urteilsaufzeichnungen des späten Mittelalters - Wallmeier, Nadine (Textsortenwandel vom 9. bis 19. Jahrhundert. Akten zur internationalen Fachtagung an der Universität Paderborn vom 9.-13.06.2015.)

Jugend als soziales Kampffeld? Die Konstruktion von Jugend und Jugendpolitiken in Europa zwischen wohlfahrtstaatlicher Regulierung und Politiken der Partizipation - Dahmen, Stephan (Jugendpolitiken. Wie geht Gesellschaft mit "ihrer" Jugend um?)

Are international accounting standards more credit relevant than domestic standards? - Florou, Annita; Kosi, Urska; Pope, Peter F (Accounting and Business Research)
We examine whether the credit relevance of financial statements, defined as the ability of accounting numbers to explain credit ratings, is higher after firms are required to report under International Financial Reporting Standards (IFRS). We find an improvement in credit relevance for firms in 17 countries after mandatory IFRS reporting is introduced in 2005; this increase is higher than that reported for a matched sample of US firms. The increase in credit relevance is particularly pronounced for higher risk speculative-grade issuers, where accounting information is predicted to be more important; and for IFRS adopters with large first-time reconciliations, where the impact of IFRS is expected to be greater. These tests provide reassurance that the overall enhancement in estimated credit relevance is driven by accounting changes related to IFRS adoption. Our results suggest that credit rating analysts’ views of economic fundamentals are more closely aligned with IFRS numbers, and that analysts anticipate at least some of the effects of the IFRS transition.
Keywords: IFRS; debt markets; credit ratings; credit relevance

Accounting quality in private firms during the transition to international standards - Valentincic, Aljosa; Novak, Ales; Kosi, Urska

Suggestions for Vocabulary Focused Reading Lessons for Mainstream Classrooms Addressing Both L1 and L2 Learners - Seifert, Susanne; Kulmhofer, Andrea; Paleczek, Lisa; Schwab, Susanne; Gasteiger-Klicpera, Barbara (Early Childhood Education Journal)
Keywords: Developmental and Educational Psychology; Education

Einsatz der Widerstandserwärmung bei hydraulischen Schneidgeräten zum Trennen von hochfesten Stahlwerkstoffen in Kraftfahrzeugen - Siewers, Bernd
Die zunehmend eingesetzten hochfesten Stähle im Automobilbau können zu schwerwiegenden Problemen bei Verkehrsunfällen führen, da hydraulische Schneidgeräte zur Befreiung von Personen an ihre mechanischen Grenzen geraten. Ein Ansatz zur Behebung dieses Problems kann die Widerstandserwärmung der zu schneidenden Werkstoffe sein. Im Rahmen dieser Dissertation wurde durch Werkstoffuntersuchungen ermittelt, dass die hochfesten Stähle einen starken Abfall der Festigkeit aufweisen, während bei denselben Temperaturen potentielle Schneidwerkstoffe deutlich höhere Festigkeiten besitzen. Das Konzept wurde schließlich in einem Funktionsmuster umgesetzt. Schneidversuche zeigten, dass durch die Widerstandserwärmung ein deutlicher Abfall der erforderlichen Schneidkraft erreicht werden konnte. Insgesamt konnte gezeigt werden, dass die Widerstandserwärmung ein vielversprechendes Konzept darstellt, um hochfeste Karosseriestähle zuverlässig und schnell zu durchtrennen und somit die Befreiung eingeschlossener Fahrzeuginsassen zu gewährleisten.
Keywords: Leichtbau; Hybridsysteme; Werkstoffe

Middlebrow and Gender: 1890-1945

The Thermal Oxidation of TiAlN High Power Pulsed Magnetron Sputtering Hard Coatings as Revealed by Combined Ion and Electron Spectroscopy - Wiesing, Martin; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Advanced Materials Interfaces)

Electric potential screening on metal targets submitted to reactive sputtering - Corbella, Carles; Marcak, Adrian; von Keudell, Achim; de los Arcos de Pedro, Maria Teresa (Journal of Vacuum Science & Technology A: Vacuum, Surfaces, and Films)

Nitridische und oxinitridische HPPMS-Beschichtungen für den Einsatz in der Kunststoffverarbeitung (Teil 1) - Bobzin, Kirsten; Grundmeier, Guido; Brögelmann, Tobias; de los Arcos de Pedro, Maria Teresa; Wiesing, Martin; Kruppe, Nathan C. (Vakuum in Forschung und Praxis)

(Cr,Al)N/(Cr,Al)ON Oxy-nitride Coatings deposited by Hybrid dcMS/HPPMS for Plastics Processing Applications - Bobzin, K.; Brögelmann, T.; Grundmeier, G.; de los Arcos de Pedro, Maria Teresa; Wiesing, M.; Kruppe, N.C. (Surface and Coatings Technology)

Influence of O2 exposure on the interaction between CH4 and amorphous AlYB14 - Hunold, Oliver; Wiesing, Martin; de los Arcos de Pedro, Maria Teresa; Music, Denis; Grundmeier, Guido; Schneider, Jochen M. (Applied Surface Science)

Revising secondary electron yields of ion-sputtered metal oxides - Corbella, Carles; Marcak, Adrian; de los Arcos de Pedro, Maria Teresa; von Keudell, Achim (Journal of Physics D: Applied Physics)

An efficient PE-ALD process for TiO2 thin films employing a new Ti-precursor - Gebhard, M.; Mitschker, F.; Wiesing, M.; Giner, I.; Torun, B.; de los Arcos de Pedro, Maria Teresa; Awakowicz, P.; Grundmeier, G.; Devi, A. (Journal of Materials Chemistry C)
A new Ti-precursor for low-temperature PE-ALD of titanium dioxide thin films as gas barrier layers on polymer substrates.

Combined Electrochemical and Electron Spectroscopic Investigations of the Surface Oxidation of TiAlN HPPMS Hard Coatings - Wiesing, Martin; to Baben, Moritz; Schneider, Jochen M.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Electrochimica Acta)

Single-Mode Parametric-Down-Conversion States with 50 Photons as a Source for Mesoscopic Quantum Optics - Harder, Georg; Bartley, Tim; Lita, Adriana E.; Nam, Sae Woo; Gerrits, Thomas; Silberhorn, Christine (Physical Review Letters)

A Stochastic Finite Element Method with a Deviatoric-volumetric Split for the Stochastic Linear Isotropic Elasticity Tensor - Mahnken, Rolf; Caylak, Ismail; Dridger, Alex (A Stochastic Finite Element Method with a Deviatoric-volumetric Split for the Stochastic Linear Isotropic Elasticity Tensor)
This paper presents a numerical method for solution of a stochastic partial differential equation (SPDE) for a linear elastic body with stochastic coefficients (random variables and/or random fields). To this end the stochastic finite element method (SFEM) is employed, which uses W IENER’S polynomial chaos expansion in order to decompose the coefficients into deterministic and stochastic parts. As a special case, we consider isotropic material behavior with two fluctuating parameters. Computational approaches involving GALERKIN projection are applied to reduce the SPDE into a system of deterministic PDEs. Furthermore, we consider normally distributed random variables, which are assumed to be stochastically independent, and which establish the number of stochastic dimensions. Subsequently, the resulting finite element equation is solved iteratively. Finally, in a representative example for a plate with a ring hole we study the influence of different variances for material parameters on the variances for the finite element results.

Modeling of variant-interaction during bainitic phase transformation - Ehlenbröker, Ulrich; Mahnken, Rolf; Petersmann, M; Antretter, T (IOP Conference Series: Materials Science and Engineering)

Extension of a multi-mechanism model: Hardness-based flow and transformation induced plasticity for austenitization - Cheng, C.; Mahnken, Rolf (International Journal of Solids and Structures)

Macromodelling of Transformation Induced Plasticity combined with Viscoplasticity for Low-Alloy Steels - Schneidt, Andreas; Mahnken, Rolf (steel research international)

Determination of effective properties for CFRP curing coupled to viscoleasticity based on a three-scale framework - Dammann, Christian; Mahnken, Rolf (PAMM)

A thermodynamic framework for coupled multiphase field and diffusion models for lower bainite transformation - Düsing, Martin; Mahnken, Rolf (PAMM)

Two accuracy improvements on nonuniform transformation field analysis for plasticity coupled to softening - Ju, Xiaozhe; Mahnken, Rolf (PAMM)

A thermodynamic framework for coupled multiphase Ginzburg-Landau/Cahn-Hilliard systems for simulation of lower bainitic transformation - Düsing, Martin; Mahnken, Rolf (Archive of Applied Mechanics)

A three-scale framework for fibre-reinforced-polymer curing part II: Mesoscopic modeling and macroscopic effective properties - Mahnken, Rolf; Dammann, Christian (International Journal of Solids and Structures)

A three-scale framework for fibre-reinforced-polymer curing Part I: Microscopic modeling and mesoscopic effective properties - Mahnken, Rolf; Dammann, Christian (International Journal of Solids and Structures)

An NTFA-based homogenization framework considering softening effects - Ju, X.; Mahnken, Rolf (Mechanics of Materials)

Design of voltage controlled oscillators (VCOs) in D-band and their phase noise measurements using frequency down-conversion - Ali, U.; Bober, M.; Thiede, Andreas (2016 11th European Microwave Integrated Circuits Conference (EuMIC))

Near infrared Kerr effect and description of field-induced phase transitions in polymer-stabilized blue phase liquid crystals - Atorf, B.; Rasouli, H.; Nordendorf, G.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

The International Liquid Crystal Society 1990–2015 - Dunmur, David; Kitzerow, Heinz-Siegfried (Liquid Crystals Today)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Comparison of Cost and Complexity for Various 16-QAM Transmitter Structures in Coherent Optical Systems - Al-Bermani, Ali; Noé, Reinhold (NEXT-GENERATION OPTICAL COMMUNICATION: COMPONENTS, SUB-SYSTEMS, AND SYSTEMS V)

Die Welt 'im schönsten Fall' - Umbruchs- und Katastrophenszenarien im Werk Angela Krauß - Morrien, Rita (Umwelt - sozial, kulturell, ökologisch. Zur Darstellung von Zeitgeschichte in deutschsprachiger Gegenwartsliteratur)

Spuren des Dialogs - literatur- und kulturwissenschaftliche Überlegungen zum Thema Dialog. 50 Jahre diplomatische Beziehungen zwischen Deutschland und Israel - Morrien, Rita (Traces of Dialogue. Symposion and exhibition 2015 between Israel/Rishon LeZion and Germany/Münster)

LiNbO3-Based Endless Optical Polarization Control The Photonic Alternative to Coherent Electronics - Noé, Reinhold; Koch, Benjamin; Mirvoda, Vitali (2016 21ST EUROPEAN CONFERENCE ON NETWORKS AND OPTICAL COMMUNICATIONS (NOC))

Time-resolved Mueller matrix measurement and polarization scrambler characterization - Koch, Benjamin; Noé, Reinhold; Mirvoda, Vitali (2016 21st European Conference on Networks and Optical Communications (NOC))

LiNbO3-based endless optical polarization control - Noé, Reinhold; Koch, Benjamin; Mirvoda, Vitali (2016 21st European Conference on Networks and Optical Communications (NOC))